Importance of religion, man and knowledge in civilizational development: Views of Malik Bennabi and Sa‘id Nursi - Berghout, Abdul Aziz (International Islamic University Malaysia (IIUM), 2013)
This article examines the views of both Malik Bennabi (1905-1973) and Sa‘Êd NËrsÊ (1878-1960) on the importance of religion, man and knowledge in civilizational development. Despite the different backgrounds, approaches, contexts and conditions the two scholars brought home the fact that these three elements make the core foundations of civilizational development. As for Malik Bennebi, this article selected the role of religion and human factors in the process of civilizational development. To him these two foundations are crucial in any developmental activity leading to progress and transformation of society. He tried to prove that religion and man are the essential foundations of human progress. As for Sa‘Êd NËrsÊ, this article selected his view of knowledge as one important foundation of civilizational development. The article concludes that, religion, man and knowledge are crucial foundations of civilizational development. It showed that both Bennabi’s and NËrsÊ’s approach to the study of the foundations of civilizational development is very much Islamic in nature.